Adrenocortical carcinosarcoma: a case report and review of the literature - Sasaki Kotaro; Desimone Marisa; Rao Harsha R; Huang George J; Seethala Raja R (BMC, 2010)
Abstract Adrenocortical carcinosarcoma is an extremely rare and aggressive variant of adrenocortical carcinoma characterized by the presence of both carcinomatous and sarcomatous components, with the latter often showing heterologous differentiation. Due to the rarity and unusual histology, it may pose a diagnostic challenge. In order to increase awareness and identify potential diagnostic pitfalls, we report the ninth case of non-functioning adrenocortical carcinosarcoma in a 45-year-old man who presented with worsening epigastric pain and a left large retroperitoneal mass in close proximity to the body/tail of pancreas and third portion of the duodenum with displacement of the kidney without parenchymal invasion and multiple liver nodules detected by computed tomographic scan. On en bloc resection, the tumor grossly did not involve the pancreas, kidney or colon. Histologically, the tumor was composed of two distinct components - an epithelioid component with granular cytoplasm that stained for synaptophysin, Melan-A, calretinin, and vimentin compatible with adrenocortical differentiation, and a pleomorphic to spindled component that was positive for desmin and myogenin, compatible with rhabdomyosarcomatous differentiation. A wedge biopsy of a liver nodule showed morphologic features similar to the epithelial component of the primary tumor. The patient died three months after surgery due to locoregional and distant recurrence. Adrenocortical carcinosarcoma is a rare malignancy that adds to the differential diagnostic considerations for a retroperitoneal epithelioid malignancy. Awareness of this as a possibility will help in distinguishing this tumor from other carcinomas, melanomas, and true sarcomas.